Maize induced resistance against downy mildew mediated by benzoic acid increased photosynthesis rate and chlorophyl content - Habibullah, Muhammad; Joko, Tri; Wibowo, Arif; Widiastuti, Ani (Universitas Lampung, 2025)
Maize downy mildew, caused by Peronosclerospora spp., is a major disease affecting maize cultivation in tropical regions, particularly in Indonesia. One potential control strategy is the induction of plant resistance. Previous studies have demonstrated that benzoic acid (BA), a non-fungicidal chemical compound, can induce maize resistance against downy mildew. Induced resistance mechanisms do not directly inhibit pathogen development but enhance the plant’s defensive response to infection. This study utilized various maize lines, ranging from susceptible to resistant, to evaluate the impact of BA-induced resistance on photosynthesis rate and chlorophyll content as the key agronomic parameters associated with the plant growth. The results showed that BA treatment did not significantly increase the photosynthetic rate and chlorophyll content in moderately resistant and resistant maize lines. However, in susceptible and moderately susceptible lines, BA treatment enhanced both parameters, indicating its role in strengthening plant resistance. These findings suggest that resistant maize lines do not respond to BA induction, whereas susceptible and moderately susceptible lines benefit significantly from its application. This provides new insight that BA can potentially induce resistance in susceptible maize plants against downy mildew.